1999
DOI: 10.1159/000028439
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Characteristics of Greek Vowels

Abstract: Five male speakers produced the vowels of Greek at slow and fast tempo, in lexically stressed and unstressed syllables, and in lexically stressed syllables of words appearing in focus position. Duration, fundamental frequency (F₀), amplitude, and the frequencies of the first (F1) and second formant (F2) were measured. The effects on these variables of the phonemic category of the vowel, tempo, stress, and focus were examined. The results indicated that the vowel system of Greek follows un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
71
1
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 29 publications
12
71
1
8
Order By: Relevance
“…In other European languages, such as Spanish (Ortega-Llebaria & Prieto, 2007) and Greek (Arvaniti, 2007;Fourakis, Botinis & Katsaiti, 1999), stress is only weakly associated with segmental quality. This permits manipulation of stress patterns independently of segmental constituency to uncover effects specific to stress, as we attempt to do in this study in the Greek language.…”
Section: Priming Stress Patterns In Word Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other European languages, such as Spanish (Ortega-Llebaria & Prieto, 2007) and Greek (Arvaniti, 2007;Fourakis, Botinis & Katsaiti, 1999), stress is only weakly associated with segmental quality. This permits manipulation of stress patterns independently of segmental constituency to uncover effects specific to stress, as we attempt to do in this study in the Greek language.…”
Section: Priming Stress Patterns In Word Recognitionmentioning
confidence: 99%
“…Stressed vowels stand out phonetically by being longer and louder than unstressed vowels (Arvaniti, 2000(Arvaniti, , 2007. Unstressed vowels exhibit only limited centralization (i.e., tendency to neutral articulation) and, crucially, there is no phonological vowel reduction associated with lack of stress (Arvaniti, 2007;Fourakis, Botinis, & Katsaiti, 1999). The Greek orthography is relatively transparent at the grapheme-phoneme level (estimated consistency 95% for reading and 80% for spelling; Protopapas & Vlahou, 2009 (Protopapas & Gerakaki, 2009).…”
Section: Knaus El Shanawany Wiese Knaus Wiese Janßen Rothermichmentioning
confidence: 99%
“…For example, it is well established that in equal conditions low vowels have a longer duration than high vowels (cf. Peterson and Lehiste [1960] and Scherba [1912] for Russian; Fourakis, Botinis, and Katsaiti [1999] for Modern Greek). The Highlow TPM and its PVI variant were meant to capture such differences.…”
Section: Text Phonological Measuresmentioning
confidence: 99%
“…In (Aulanko, 1985;Whalen and Levitt, 1995;Monaghan, 1992;Vainio, 2001) has been pointed out the role of segmental prosody to the F 0 surface, such as the fundamental frequency difference between open and close vowels. In Greek, F 0 differences caused by the phonemic content do not follow the universal tendencies (Fourakis et al, 1999). In (Arvaniti et al, 1998) it was also shown that the alignment of the H target in the pre-nuclear L * + H accent is also affected by the segment type (stop, fricative, nasal) of the phoneme that precedes the post-accentual vowel.…”
Section: Feature Setmentioning
confidence: 99%